Effect of Silica Fume Concentration and Water–Cement Ratio on the Compressive Strength of Cement-Based Mortars - Badalyan, Maria M.; Muradyan, Nelli G.; Shainova, Roza S.; Arzumanyan, Avetik A.; Kalantaryan, Marine A.; Sukiasyan, Rafayel R.; Yeranosyan, Mkrtich; Laroze, David; Vardanyan, Yeghiazar V.; Barseghyan, Manuk G. (Buildings (Basel), 2024)
This study investigated how the water–cement ratio and silica fume concentration affect the compressive strength of cement mortars. This comprehensive study delved into the intricate interplay between water–cement ratio and silica fume concentration, examining their influence on cement-based mortars’ compressive strength and water absorption characteristics. The silica fume concentration was investigated, ranging from 5% to 15% of the cement weight. The investigation employed two distinct mixing techniques, mixing cement and silica fume, before extracting appropriate samples; alternatively, a magnetic stirrer was used to prepare samples by dissolving silica fume in water. The cement mortars were also prepared with three different water–cement ratios: 0.44, 0.47, and 0.5. The interesting findings of compressive tests illuminated a consistent trend across all curing days and mixing methods—a reduction in the water–cement ratio corresponded with a notable increase in compressive strength. However, it is essential to note that the influence of the mixing method on the compressive strength of cement-based mortars is based on the water–cement ratio. The results show that by using the suggested technological method, it was observed that samples prepared with water–cement ratios (W/C) of 0.47 and 0.44 exhibited higher compressive strengths compared to those prepared using the well-known standard mixing method. The compressive test results underscored that the water–cement ratio reduction consistently enhanced the compressive strength in every combination of curing days and mixing techniques. Furthermore, this reduction in the water–cement ratio was correlated with a decrease in water absorption of the mortar. Conversely, the water–cement ratio itself played a pivotal role in defining how the mixing technique affected the compressive strength and water absorption of cement-based mortars. This multifaceted exploration underscores the nuanced relationships between key variables, emphasizing the need for a comprehensive understanding of the intricate factors influencing the mechanical and absorptive properties of cement-based materials.